VALIDATION OF FULL CORE GEOMETRY MODEL OF THE NODAL3 CODE IN THE PWR TRANSIENT BENCHMARK PROBLEMS - Tagor Malem Sembiring; Surian Pinem; Peng Hong Liem (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2015)
ABSTRACT VALIDATION OF FULL CORE GEOMETRY MODEL OF THE NODAL3 CODE IN THE PWR TRANSIENT BENCHMARK PROBLEMS. The coupled neutronic and thermal-hydraulic (T/H) code, NODAL3 code, has been validated in some PWR static benchmark and the NEACRP PWR transient benchmark cases. However, the NODAL3 code have not yet validated in the transient benchmark cases of a control rod assembly (CR) ejection at peripheral core using a full core geometry model, the C1 and C2 cases.  By this research work, the accuracy of the NODAL3 code for one CR ejection or the unsymmetrical group of CRs ejection case can be validated. The calculations by the NODAL3 code have been carried out by the adiabatic method (AM) and the improved quasistatic method (IQS). All calculated transient parameters by the NODAL3 code were compared with the reference results by the PANTHER code. The maximum relative difference of 16% occurs in the calculated time of power maximum parameter by using the IQS method, while the relative difference of the AM method is 4% for C2 case.  All calculation results by the NODAL3 code shows there is no systematic difference, it means the neutronic and T/H modules are adopted in the code are considered correct. Therefore, all calculation results by using the NODAL3 code are very good agreement with the reference results. Keywords: nodal method, coupled neutronic and thermal-hydraulic code, PWR, transient case, control rod ejection.  ABSTRAK VALIDASI MODEL GEOMETRI TERAS PENUH PAKET PROGRAM NODAL3 DALAM PROBLEM BENCHMARK GAYUT WAKTU PWR. Paket program kopel neutronik dan termohidraulika (T/H), NODAL3, telah divalidasi dengan beberapa kasus benchmark statis PWR dan kasus benchmark gayut waktu PWR NEACRP.  Akan tetapi, paket program NODAL3 belum divalidasi dalam kasus benchmark gayut waktu akibat penarikan sebuah perangkat batang kendali (CR) di tepi teras menggunakan model geometri teras penuh, yaitu kasus C1 dan C2. Dengan penelitian ini, akurasi paket program NODAL3 untuk kasus penarikan sebuah CR atau sekelompok CR yang tidak-simetris dapat divalidasi.  Perhitungan paket program NODAL3 dilakukan dengan metode adiabatic (AM) dan improved quasistatic (IQS).  Seluruh parameter gayut waktu hasil perhitungan paket program NODAL3 dibandingkan dengan hasil acuan dengan paket program PANTHER. Perbedaan relatif maksimum sebesar 16% terjadi dalam perhitungan parameter waktu daya maksimum dengan metode IQS pada kasus C2, sedangkan perbedaan relatif dengan metode AM adalah 4%. Seluruh hasil perhitungan dengan paket program NODAL3 menunjukkan tidak adanya perbedaan yang sistematis, berarti modul neutronik dan T/H yang diadopsi di NODAL3 sudah benar. Oleh karena itu, seluruh perhitungan dengan paket program NODAL3 sangat sesuai dengan hasil acuan. Kata kunci: metode nodal, paket program kopel neutonik dan termo-hidrolika, kasus gayut-waktu, tertariknya batang kendali.